The Changes of Amygdala Transcriptome in Autism Rat Model After Arginine Vasopressin Treatment - Zhou, Bo; Zheng, Xiaoli; Chen, Yunhua; Yan, Xuehui; Peng, Jinggang; Liu, Yibu; Zhang, Yi; Tang, Lei; Wen, Min (Frontiers in Neuroscience, 2022)
Background Some studies have shown that arginine vasopressin (AVP) can significantly improve the social interaction disorder of autism, but the mechanism remains unclear. Methods Female Wistar rats were intraperitoneally injected with VPA or normal saline at embryonic day 12.5 to establish an autism model or normal control in their offspring. Male offspring prenatally exposed to VPA were randomly assigned to two groups: the VPA-induced autism model group and the AVP group. The rats in the AVP group were treated with intranasal AVP at postnatal day (PND) 21 and for 3 weeks. The VPA-induced autism model group was given the same dose of normal saline in the same way. Behavioral responses were evaluated in the open field and three-chambered social test apparatus; the expression levels of AVP in serum were detected by enzyme-linked immunosorbent assay kit, and the gene expression levels on the amygdala were measured by RNA-seq at PND42. Results Intranasal administration of AVP can significantly improve the social interaction disorder and elevate the levels of AVP in serum. Transcriptome sequencing results showed that 518 differently expressed genes (DEGs) were identified in the VPA-induced autism model group compared with the control in this study. Gene Ontology biological process enrichment analysis of DEGs showed that the VPA-induced autism model group had significant nervous system developmental impairments compared with the normal group, particularly in gliogenesis, glial cell differentiation, and oligodendrocyte differentiation. Gene Set Enrichment Analysis (GSEA) enrichment analysis also showed that biological process of oligodendrocyte differentiation, axoneme assembly, and axon ensheathment were inhibited in the VPA-induced autism model group. Pathway enrichment analysis of DEGs between the control and VPA-induced autism model group showed that the PI3K/AKT and Wnt pathways were significantly dysregulated in the VPA-induced autism model group. Few DEGs were found when compared with the transcriptome between the VPA-induced autism model group and the AVP treatment group. GSEA enrichment analysis showed deficits in oligodendrocyte development and function were significantly improved after AVP treatment; the pathways were mainly enriched in the NOTCH, mitogen-activated protein kinase, and focal adhesion signaling pathways, but not in the PI3K/AKT and Wnt pathways. The expression patterns analysis also showed the same results. Conclusion AVP can significantly improve the social interaction disorder of VPA-induced autism model, and AVP may target behavioral symptoms in autism by modulating the vasopressin pathways, rather than primary disease mechanisms.